2018
DOI: 10.3389/fmicb.2018.02703
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A Strain of an Emerging Indian Xanthomonas oryzae pv. oryzae Pathotype Defeats the Rice Bacterial Blight Resistance Gene xa13 Without Inducing a Clade III SWEET Gene and Is Nearly Identical to a Recent Thai Isolate

Abstract: The rice bacterial blight pathogen Xanthomonas oryzae pv. oryzae (Xoo) injects transcription activator-like effectors (TALEs) that bind and activate host “susceptibility” (S) genes important for disease. Clade III SWEET genes are major S genes for bacterial blight. The resistance genes xa5, which reduces TALE activity generally, and xa13, a SWEET11 allele not recognized by the cognate TALE, have been effectively deployed. However, strains that defeat both resistance genes individually were recently reported in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It has been reported that Xa41(t) (having 18 bp deletion) offers broad-spectrum resistance against a large collection of Xoo strains (Hutin et al, 2015b). Recently it was reported that some Xoo strains still cause infection in rice despite R genes (Carpenter et al, 2018;Doucouré et al, 2018). These failures have prompted plant genome engineers to develop resistance against this rapidly evolving pathogen by mutating susceptibility genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Xa41(t) (having 18 bp deletion) offers broad-spectrum resistance against a large collection of Xoo strains (Hutin et al, 2015b). Recently it was reported that some Xoo strains still cause infection in rice despite R genes (Carpenter et al, 2018;Doucouré et al, 2018). These failures have prompted plant genome engineers to develop resistance against this rapidly evolving pathogen by mutating susceptibility genes.…”
Section: Discussionmentioning
confidence: 99%
“…R gene xa5 showed very good resistance (above 95%) to Xoo from all lineages. Previously, isolates of Xoo having compatibility with xa5 were only reported from Indian Lineages IX-I and IX-III, and some Philipps and Korea isolates (35, 5557). The only 2 Chinese Xoo from Yunnan province (YN24 and YN04-5) belonging to IX-I and IX-III showed good infection ability to rice with xa5 , suggesting putative transmission of Xoo from India to South China.…”
Section: Discussionmentioning
confidence: 99%
“…The positive regulatory nature of SWEET s was reported in rice and cotton against the blight pathogen X. citri . In rice, the recessive resistance genes xa13 and xa25 are the mutant forms of SWEET11 and SWEET14 , respectively, and play a positive role in resistance against Xoo (Carpenter et al, 2018). In cotton, the recessive gene b6 (a homolog of SWEET gene) is involved in the resistance response against X. citri in the Acb6 line (Acala‐44 cotton line with the b6 gene; Cox et al, 2017).…”
Section: Sweet Family Transportersmentioning
confidence: 99%